Preparation method and application of Co-M LDHs (at) ZIF-67 composite film layer on surface of magnesium alloy MAO film
By forming the Co-M LDHs@ZIF-67 composite film layer on the surface of the microarc oxide film of magnesium alloy, the problems of poor corrosion and high MOFs consumption in humid environments are solved, and a longer lasting and environmentally friendly corrosion resistance is achieved. , suitable for aviation, automobile and other fields.
Patent Information
- Application Number
- CN202411372092.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
The existing microarc oxide film of magnesium alloy has pores and microcracks, which leads to poor corrosion in water and humid environments. The single-layer protection effect of LDHs is not long-lasting. MOFs are limited in barrier properties and consume large amounts when applied to the surface of magnesium alloy. It is safe. Poor performance and environmental performance.
The preparation method of the Co-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy microarc oxide film is adopted. Through microarc oxidation treatment, in-situ hydrothermal reaction and coordination complexation reaction, a dense Co-M LDHs@ZIF is formed. -67 composite membrane layer, using Co2+ to participate in ZIF-67 nucleation growth, sealing the pores of the MAO membrane and preventing corrosion of the medium.
It significantly improves the corrosion resistance and corrosion resistance of magnesium alloys, reduces production costs and energy consumption, simplifies the process flow, enhances the bonding between the film layer and the substrate, and is suitable for applications in aviation, automobiles and other fields.
Smart Images

Figure CN119242176A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface protection treatment, and specifically relates to a preparation method and application of a Co-M LDHs@ZIF-67 composite film layer on the surface of a magnesium alloy micro-arc oxidation film. Background Art
[0002] Magnesium and magnesium alloys are the lightest structural metals. With the rapid development of science and technology, magnesium alloys, as a lightweight and high-strength metal with good electrical and thermal conductivity, have been widely used in aviation, automobiles, electronics and other fields. However, due to its low standard electrode potential, it is easy to corrode in water and humid environments, which limits its wider application. In order to improve the corrosion resistance of magnesium alloys, surface treatment technology has become the main way to improve the corrosion resistance of magnesium alloys.
[0003] Micro-arc oxidation (MAO) film has attracted attention because it can form a dense ceramic layer and improve the corrosion resistance and wear resistance of magnesium alloys. However, there are inherent pores and microcracks on the surface of a single MAO coating. These micropores and cracks are connecting channels for corrosive media to invade the substrate, making the protection effect of the MAO film layer unsatisfactory in some harsh environments. Therefore, it is necessary to post-treat the MAO film layer to improve its protective performance.
[0004] Layered Double Hydroxides (LDHs), as a new type of inorganic material, have been widely used in the field of corrosion protection due to their unique interlayer structure and ion exchange properties. There are many types of LDHs coatings, such as Mg-Al LDHs, Zn-Al LDHs, and Co-Al LDHs. A large number of studies have shown that they can provide good physical barriers and chemical stability for alloys. However, single LDHs have interlayer gaps, and their long-term protection is not ideal. In order to ensure its anti-corrosion effect, LDHs can be doped with other materials for composite growth.
[0005] Metal-organic frameworks (MOFs), porous materials composed of organic linkers and metal ions, are also used in the field of corrosion protection. Zeolitic imidazolate framework (ZIF) is an inorganic material with unique structure and properties. It is simple to prepare, non-toxic to the human body and the environment, and has good physical barriers and chemical stability. Therefore, it is widely used in protective coatings for magnesium alloys. Although MOFs materials have many advantages, there are still some challenges in practical applications. For example, a single MOF has a microporous / mesoporous structure, which makes it limited in its barrier to corrosive media. Moreover, on the untreated alloy surface, MOFs not only cannot form a film directly, but also destroy the corrosion resistance of the alloy itself. Therefore, MAO, LDHs and MOFs can be combined to prepare a composite film layer to improve the problem that a single film layer cannot form a film / the protective performance is not durable enough, thereby improving the corrosion resistance of magnesium alloys. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a method for preparing a Co-M LDHs@ZIF-67 composite film layer on the surface of a magnesium alloy micro-arc oxidation film, aiming to solve the problems that the existing MAO has many pores, the protective effect of LDHs in the field of magnesium alloy corrosion protection is not persistent and unstable, the application of MOFs in magnesium alloy corrosion protection is not extensive, the preparation of raw materials is diverse, the consumption is large, and the safety, environmental protection and energy-saving performance are poor.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a Co-M LDHs@ZIF-67 composite film layer on the surface of a magnesium alloy micro-arc oxidation film comprises the following steps:
[0009] 1) immersing the magnesium alloy in a micro-arc oxidation growth solution for micro-arc oxidation treatment to obtain a magnesium alloy covered with a MAO layer;
[0010] 2) immersing the magnesium alloy coated with the MAO layer into an in-situ growth solution for in-situ hydrothermal reaction, washing and drying, and obtaining a magnesium alloy coated with a Co-M LDHs film layer;
[0011] 3) The magnesium alloy coated with the Co-M LDHs film layer is immersed in a ZIF-67 growth solution for coordination complex reaction, and then washed and dried to obtain a magnesium alloy coated with a Co-M LDHs@ZIF-67 composite film layer, i.e., a Co-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film.
[0012] In certain specific embodiments, the micro-arc oxidation growth solution includes an aqueous solution of 0.03-0.06 M trisodium phosphate dodecahydrate and 0.1-0.3 M sodium hydroxide, measured in terms of molar concentration.
[0013] In some specific embodiments, the process parameters of the micro-arc oxidation treatment are: the temperature of the micro-arc oxidation growth liquid is 5-10° C., the voltage of the micro-arc oxidation treatment is 300-400 V, and the time is 2-8 min.
[0014] In some specific embodiments, the in-situ growth solution includes, in terms of molar concentration, a mixed aqueous solution of 0.1-0.2 M cobalt nitrate, 0.05-0.1 M sodium nitrate, and any one of 0.03-0.08 M iron nitrate, 0.03-0.08 M aluminum nitrate, or 0.03-0.08 M nickel nitrate.
[0015] In certain specific embodiments, the process parameters of the in-situ hydrothermal reaction are: reaction temperature of 125-145° C., and reaction time of 8-16 h.
[0016] In certain specific embodiments, the ZIF-67 growth solution includes a mixed aqueous solution of 0.01-0.04 M cobalt nitrate and 1.0-1.5 M dimethylimidazole, measured in terms of molar concentration.
[0017] In certain specific embodiments, the process parameters of the coordination complex reaction are: reaction temperature is room temperature of 20-30° C., and reaction time is 16-32 h.
[0018] In some specific embodiments, the magnesium alloy is also pretreated before the micro-arc oxidation treatment, specifically: the magnesium alloy substrate is polished using 150, 600, 800, 1200, and 2000# sandpaper, and ultrasonically cleaned with alcohol and then dried; then the polished magnesium alloy substrate is degreased and deoiled.
[0019] In certain specific embodiments, the degreasing and deoiling solution used in the degreasing and deoiling process is an aqueous solution including 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate, measured by mass concentration and by mass volume concentration.
[0020] The Co-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared by the aforementioned preparation method is used in the fields of aerospace, automobile, medical equipment and 3C digital.
[0021] Compared with the prior art, the present invention has at least the following advantages:
[0022] 1) The preparation method provided in the present application adopts a micro-arc oxidation (MAO) growth solution of specific components, the components of which are simple and easy to obtain, which greatly shortens the time of micro-arc oxidation treatment to only 2-8 minutes, greatly improving the production efficiency; the Co-M LDHs film layer grown in situ on the MAO film layer has good bonding force and film-forming properties, and closes the pores of the MAO film; the Co in the LDHs film layer 2+ Participate in the formation of ZIF-67 film, effectively block and prevent external corrosive ions (such as Cl - etc.) to the corrosion of magnesium substrate, thus protecting the substrate;
[0023] 2) The preparation method of the present application is based on Co 2+ (central ion of ZIF-67) is the central cation of LDHs. Various Co-M LDHs were prepared by the traditional one-step hydrothermal method. When preparing ZIF-67, Co in the LDHs membrane layer 2+ It becomes the nucleation site of ZIF-67, inducing the "nucleation-growth" process of ZIF-67 crystals, so that the present invention has better corrosion protection effect than a single film layer, and the preparation method of the present invention is more mature, has the advantages of more energy saving, more industrial production practicability, simple operation, etc., and provides a new technical route for industrial production;
[0024] 3) The method for preparing the Co-M LDHs@ZIF-67 composite film layer on the surface of the micro-arc oxidation film of the magnesium alloy provided by the present invention comprises the following steps: firstly performing micro-arc oxidation treatment on the magnesium alloy, then performing an in-situ growth reaction on the magnesium alloy after the micro-arc oxidation treatment by a conventional one-step in-situ hydrothermal method in a reactor, and finally obtaining a uniform and dense Co-MLDHs@ZIF-67 composite film layer through coordination and complexation at room temperature; the reagents used in the entire preparation process are simple, easy to obtain, and pollution-free to the environment; the overall process is simple and green and environmentally friendly, which can meet the needs of industrial development and mass production, and can further expand the application scope of magnesium alloys, and is suitable for promotion and application in aerospace, automobile, medical equipment, 3C digital and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0026] Figure 1 is a scanning electron microscope photograph of the Co-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 1;
[0027] Figure 2 is the XRD spectrum of the Co-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 1;
[0028] Figure 3 The Tafel polarization curves of AZ31 magnesium alloy, AZ31 magnesium alloy coated with MAO film, AZ31 magnesium alloy coated with Co-Fe LDHs film, AZ31 magnesium alloy coated with ZIF-67 and AZ31 magnesium alloy coated with Co-Fe LDHs@ZIF-67 composite film layer measured by electrochemical workstation in Example 1, Comparative Example 1 and Comparative Example 2 under the same coordinates;
[0029] Figure 4 is a scanning electron microscope photograph of the Co-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 2;
[0030] Figure 5 is the XRD spectrum of the Co-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 2;
[0031] Figure 6 AZ31 magnesium alloy, AZ31 magnesium alloy coated with MAO film and AZ31 magnesium alloy coated with Co-Al LDHs@ZIF-67 composite film layer measured by electrochemical workstation in Example 2 under the same coordinates;
[0032] Figure 7 is a scanning electron microscope photograph of the Co-Ni LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 3;
[0033] Figure 8 is the XRD spectrum of the Co-Ni LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 3;
[0034] Fig. 9 AZ31 magnesium alloy, AZ31 magnesium alloy coated with MAO film and AZ31 magnesium alloy coated with Co-Ni LDHs@ZIF-67 composite film layer measured by electrochemical workstation in Example 3 under the same coordinates;
[0035] Fig.10 The cross-sectional SEM and surface area element EDS distribution diagram of the Co-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared in Examples 1-3;
[0036] Fig.11 The durability test results of the Co-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared in Examples 1-3 are Tafel polarization curves at the same coordinates after the composite film layer is immersed in a 3.5wt% NaCl solution for 14 days;
[0037] Fig.12 This is the XRD spectrum of the ZIF-67@Co-M LDHs composite film layer on the surface of the magnesium alloy MAO film prepared in Comparative Example 3. DETAILED DESCRIPTION
[0038] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0039] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0040] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0041] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0042] In the following examples, cobalt nitrate, sodium nitrate, ferric nitrate, aluminum nitrate, nickel nitrate, anhydrous ethanol, and deionized water were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd., China;
[0043] In the following examples, the corrosion resistance is reflected by testing the Tafel polarization curve of each test sample.
[0044] Example 1
[0045] The method for preparing the Co-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film provided in this embodiment comprises the following steps:
[0046] 1) Preprocessing
[0047] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0048] 12) Magnesium alloy pretreatment: Use 150#, 600#, 800#, 1200#, and 2000# sandpaper to grind the magnesium alloy, and use alcohol to ultrasonically clean it for five minutes and then dry it for use;
[0049] 13) Soak the polished magnesium alloy AZ31 in the above degreasing and deoiling aqueous solution, keep it in a water bath at 50°C for 60 seconds, then wash it with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polish it with 400g / L nitric acid (ρ=1.42g / ml) at room temperature 25°C for 2 minutes; then wash it once with deionized water and blow it dry with cold air;
[0050] 2) Micro-arc oxidation film (MAO film for short)
[0051] 21) Prepare a micro-arc oxidation growth solution containing 0.049 M trisodium phosphate dodecahydrate and 0.18 M sodium hydroxide using deionized water according to the molar concentration;
[0052] 22) First, the magnesium alloy sample after degreasing and deoiling in step 1) is fixed in a polymethyl methacrylate electrolytic cell equipped with a stainless steel plate by copper wire, and then the micro-arc oxidation growth solution in step 21) is poured; the anode is AZ31 magnesium alloy, and the cathode is a stainless steel plate; the temperature of the micro-arc oxidation growth solution is 8°C, the reaction voltage is 350V, and the reaction time is 5min, to obtain a magnesium alloy covered with a MAO film;
[0053] 3) In situ growth of Co-Fe LDHs film
[0054] 31) According to the molar concentration, sodium nitrate, cobalt nitrate and ferric nitrate are dissolved in deionized water and mixed evenly to obtain an in-situ growth solution; wherein the molar concentration of sodium nitrate is 0.1 M, the molar concentration of cobalt nitrate is 0.15 M, and the molar concentration of ferric nitrate is 0.05 M; and then the pH value thereof is adjusted to 12 using a 0.1 M NaOH aqueous solution;
[0055] 32) Putting the magnesium alloy coated with MAO film prepared in step 2) into a polytetrafluoroethylene liner sleeve, then pouring the in-situ growth solution prepared in step 31) into the liner and placing the liner into the reactor, tightening it, and finally placing it in a drying oven for in-situ growth, the reaction temperature is 135° C., the reaction time is 12 h, and then washing and drying to obtain a magnesium alloy coated with Co-Fe LDHs film;
[0056] The cleaning and drying is specifically to first use running deionized water to clean the magnesium alloy sample covered with the Co-Fe LDHs film layer after the reaction in step 3) to remove the in-situ growth liquid attached to the surface, then put it into an ultrasonic cleaning machine in anhydrous ethanol for ultrasonic cleaning for 3 minutes, then clean it with deionized water, and dry it to obtain the Co-Fe LDHs film layer on the surface of the magnesium alloy micro-arc oxidation film;
[0057] 4) Coordination complex growth of ZIF-67 membrane
[0058] 41) Prepare two aqueous solutions containing 0.02 M cobalt nitrate and 1.4 M dimethylimidazole respectively;
[0059] 42) The magnesium alloy coated with the Co-Fe LDHs film layer prepared in step 3) is immersed in a mixed solution of the above two aqueous solutions, maintained at room temperature 25°C for 25 hours for coordination and complexation, and then washed and dried to obtain a magnesium alloy coated with a Co-Fe LDHs@ZIF-67 composite film layer; washed with deionized water and dried to obtain a Co-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film.
[0060] The present application tests the morphology, structure and performance of the Co-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film prepared in this embodiment, specifically:
[0061] 1) Appearance
[0062] The present application conducted an appearance morphology test on the Co-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy in Example 1. The electron microscope scanning image is shown in FIG. Figure 1 As shown in the figure, it can be seen that the Co-Fe LDHs nanosheets grown on the surface of the magnesium alloy MAO film are small in size, the pores formed between the sheets are large, and the density is poor; after the Co-Fe LDHs@ZIF-67 composite film layer is grown, the LDHs nanosheets become larger, the ZIF-67 grains on the surface are obvious, and the density of the composite film layer is significantly improved.
[0063] 2) Structural analysis
[0064] The present application tests the crystallinity of the Co-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film in Example 1. The XRD spectrum is as follows: Figure 2 As shown in the figure, (003) and (006) crystal planes are characteristic crystal planes of LDHs. It can be seen from the figure that the Co-Fe LDHs coating has been successfully prepared. The diffraction peaks of the Co-Fe LDHs@ZIF-67 composite coating at 7.31°, 10.36°, 12.72°, 14.40°, 16.45° and 18.04° correspond to the (011), (002), (112), (013), (022) and (222) crystal planes of ZIF-67, respectively, indicating that it has good crystallinity.
[0065] 3) Electrochemical performance
[0066] The present application tests the electrochemical properties of the Co-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy in Example 1 by an electrochemical workstation. In addition, the electrochemical properties of Comparative Examples 1 and 2 are used for comparison, specifically:
[0067] The Tafel polarization curves of magnesium alloy AZ31, magnesium alloy coated with MAO film (curve MAO), magnesium alloy coated with Co-FeLDHs film (curve Co-Fe LDHs), magnesium alloy coated with ZIF-67 film (curve ZIF-67) and magnesium alloy coated with Co-FeLDHs@ZIF-67 composite film (curve Co-Fe LDHs@ZIF-67) under the same coordinates measured by electrochemical workstation are as follows: Figure 3 Specifically:
[0068] The corrosion resistance test of the magnesium alloy protective film is represented by the electrochemical polarization curve (the equipment model is Princeton4000A), in which the corrosion voltage of the AZ31 magnesium alloy is -1.37V, the corrosion voltage of the AZ31 magnesium alloy coated with the Co-Fe LDHs film after the treatment of the comparative example 1 is -1.51V, the corrosion voltage of the AZ31 magnesium alloy coated with the ZIF-67 film after the treatment of the comparative example 2 is -1.49V, the corrosion voltage of the AZ31 magnesium alloy coated with the MAO film after the treatment of the embodiment 1 is -1.55V, and the corrosion voltage of the AZ31 magnesium alloy coated with the Co-Fe LDHs@ZIF-67 composite film is -0.99V, which is significantly improved compared with the corrosion voltage of the magnesium alloy substrate, and the corrosion tendency is reduced. The corrosion rate and corrosion resistance are directly related to the corrosion current density. The corrosion current density of pure AZ31 magnesium alloy is 1.02×10 -5 Acm -2 The corrosion current density of the AZ31 magnesium alloy coated with Co-Fe LDHs film after treatment under the conditions of Comparative Example 1 is 7.62×10 -7 A cm -2 The corrosion current density of the AZ31 magnesium alloy coated with ZIF-67 film after treatment under the conditions of Comparative Example 2 is 7.44×10 -4 A cm -2 However, the corrosion current density of the magnesium alloy coated with MAO film after treatment under the conditions of Example 1 is 3.86×10 -6 A cm -2 The corrosion current density of the magnesium alloy coated with Co-Fe LDHs@ZIF-67 composite film is 4.25×10 -9 A cm -2. Compared with the sample of AZ31 magnesium alloy, the corrosion current density is reduced by 4 orders of magnitude; compared with the magnesium alloy coated with MAO film, the corrosion current density is reduced by 3 orders of magnitude; compared with the magnesium alloy coated with Co-Fe LDHs film, the corrosion current density is reduced by 2 orders of magnitude; compared with the magnesium alloy coated with ZIF-67 film, the corrosion current density is reduced by 5 orders of magnitude. What is special is that the electrochemical performance of the ZIF-67 film on the surface of magnesium alloy is one order of magnitude higher than that of the untreated AZ31 substrate. This is because it is difficult for ZIF-67 nanoparticles to form a film on the surface of magnesium alloy, and a small amount of aggregated nanoparticles become the invasion point of the corrosive medium. Therefore, the MOFs film layer cannot exist alone on the surface of magnesium alloy. The above results can fully explain that the Co-Fe LDHs@ZIF-67 composite film on the surface of magnesium alloy MAO film has an effective corrosion inhibition effect on AZ31 magnesium alloy, and it has better corrosion resistance than the single MAO, LDHs and ZIF-67 films. The Co-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film of the present invention has excellent corrosion resistance and can effectively protect the magnesium substrate.
[0069] Example 2
[0070] The method for preparing the Co-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film provided in this embodiment comprises the following steps:
[0071] 1) Preprocessing
[0072] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0073] 12) Magnesium alloy pretreatment: Use 150#, 600#, 800#, 1200#, and 2000# sandpaper to grind the magnesium alloy, and use alcohol to ultrasonically clean it for five minutes and then dry it for use;
[0074] 13) Soak the polished magnesium alloy AZ31 in the above degreasing and deoiling aqueous solution, keep it in a water bath at 50°C for 60 seconds, then wash it with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polish it with 400g / L nitric acid (ρ=1.42g / ml) at room temperature 25°C for 2 minutes; then wash it once with deionized water and blow it dry with cold air;
[0075] 2) Micro-arc oxidation film (MAO film for short)
[0076] 21) Prepare a micro-arc oxidation growth solution containing 0.049 M trisodium phosphate dodecahydrate and 0.18 M sodium hydroxide using deionized water according to the molar concentration;
[0077] 22) First, the magnesium alloy sample after degreasing and deoiling in step 1) is fixed in a polymethyl methacrylate electrolytic cell equipped with a stainless steel plate by copper wire, and then the micro-arc oxidation growth solution in step 21) is poured; the anode is AZ31 magnesium alloy, and the cathode is a stainless steel plate; the temperature of the micro-arc oxidation growth solution is 8°C, the reaction voltage is 350V, and the reaction time is 5min, to obtain a magnesium alloy covered with a MAO film;
[0078] 3) In situ growth of Co-Al LDHs film
[0079] 31) According to the molar concentration, sodium nitrate, cobalt nitrate and aluminum nitrate are dissolved in deionized water and mixed evenly to obtain an in-situ growth solution; wherein the molar concentration of sodium nitrate is 0.1 M, the molar concentration of cobalt nitrate is 0.15 M, and the molar concentration of aluminum nitrate is 0.05 M; and then the pH value thereof is adjusted to 8 using a 0.1 M NaOH aqueous solution;
[0080] 32) Putting the magnesium alloy coated with MAO film prepared in step 2) into a polytetrafluoroethylene liner sleeve, then pouring the in-situ growth solution prepared in step 31) into the liner and placing the liner into the reactor, tightening it, and finally placing it in a drying oven for in-situ growth, the reaction temperature is 135° C., the reaction time is 12 h, and then washing and drying to obtain a magnesium alloy coated with Co-Al LDHs film;
[0081] The cleaning and drying is specifically to first use running deionized water to clean the magnesium alloy sample covered with the Co-Al LDHs film layer after the reaction in step 3) to remove the in-situ growth liquid attached to the surface, then put it into an ultrasonic cleaning machine in anhydrous ethanol for ultrasonic cleaning for 3 minutes, then clean it with deionized water, and dry it to obtain the Co-Al LDHs film layer on the surface of the magnesium alloy micro-arc oxidation film;
[0082] 4) Coordination complex growth of ZIF-67 membrane
[0083] 41) Prepare two aqueous solutions containing 0.02 M cobalt nitrate and 1.4 M dimethylimidazole respectively;
[0084] 42) The magnesium alloy coated with the Co-Al LDHs film layer prepared in step 3) is immersed in a mixed solution of the above two aqueous solutions, maintained at room temperature 25°C for 25 hours for coordination and complexation, and then washed and dried to obtain a magnesium alloy coated with a Co-Al LDHs@ZIF-67 composite film layer; washed with deionized water and dried to obtain a Co-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film.
[0085] The present application tests the morphology, structure and performance of the Co-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film prepared in this embodiment, specifically:
[0086] 1) Appearance
[0087] The present application conducted an appearance morphology test on the Co-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film in Example 2. The electron microscope scanning image is shown in FIG. Figure 4 As shown in the figure, it can be seen that the Co-Al LDHs nanosheets grown on the surface of the magnesium alloy MAO film grow parallel to the substrate and are uniform in size, but there are large gaps between the LDHs layers; after the growth of the Co-AlLDHs@ZIF-67 composite film layer, the LDHs nanosheets become honeycomb-shaped, and the ZIF-67 grains on the surface grow between the LDHs layers and on their surfaces with different sizes, but the density of the composite film layer is significantly improved.
[0088] 2) Structural analysis
[0089] The present application tests the crystallinity of the Co-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film in Example 2. The XRD spectrum is shown in FIG. Figure 5 As shown in the figure, (003) and (006) crystal planes are the characteristic crystal planes of LDHs. It can be seen from the figure that the Co-Al LDHs coating has been successfully prepared. The diffraction peaks of the Co-Al LDHs@ZIF-67 composite coating at 7.31°, 10.36°, 12.72°, 14.40°, 16.45° and 18.04° correspond to the (011), (002), (112), (013), (022) and (222) crystal planes of ZIF-67, respectively, indicating that it has good crystallinity.
[0090] 3) Electrochemical performance
[0091] The present application tests the electrochemical properties of the magnesium alloy surface film layer in Example 2 by using an electrochemical workstation, specifically:
[0092] The Tafel polarization curves of magnesium alloy AZ31, magnesium alloy coated with MAO film (curve MAO) and magnesium alloy coated with Co-Al LDHs@ZIF-67 composite film (curve Co-Al LDHs@ZIF-67) at the same coordinates measured by electrochemical workstation are as follows: Figure 6 As shown, specifically:
[0093] The corrosion resistance test of the magnesium alloy protective film is represented by the electrochemical polarization curve (equipment model is Princeton4000A), in which the corrosion voltage of AZ31 magnesium alloy is -1.37V, the corrosion voltage of AZ31 magnesium alloy coated with MAO film after treatment under the conditions of Example 2 is -1.55V, and the corrosion voltage of AZ31 magnesium alloy coated with Co-Al LDHs@ZIF-67 composite film is -0.88V, which is significantly improved compared with the corrosion voltage of magnesium alloy substrate, and the corrosion tendency is reduced. The corrosion rate and corrosion resistance are directly related to the corrosion current density. The corrosion current density of pure AZ31 magnesium alloy is 1.02×10 -5 Acm -2 The corrosion current density of the magnesium alloy covered with MAO film is 3.86×10 -6 A cm -2 However, the corrosion current density of the magnesium alloy coated with Co-AlLDHs@ZIF-67 composite film after treatment under the conditions of Example 2 is 2.97×10 -9 A cm -2 The corrosion current density of the treated magnesium alloy is reduced by 3 orders of magnitude compared with the magnesium alloy coated with MAO film; the corrosion current density is reduced by 4 orders of magnitude compared with the sample of AZ31 magnesium alloy. The above results can fully illustrate that the Co-Al LDHs@ZIF-67 composite film has an effective corrosion inhibition effect on AZ31 magnesium alloy, and the Co-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film of the present invention has excellent corrosion resistance and can effectively protect the magnesium substrate.
[0094] Example 3
[0095] The method for preparing the Co-Ni LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film provided in this embodiment comprises the following steps:
[0096] 1) Preprocessing
[0097] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0098] 12) Pretreatment of magnesium alloy: using 150#, 600#, 800#, 1200#, and 2000# sandpaper to grind the magnesium alloy, and using alcohol to ultrasonically clean it for five minutes and then dry it for use;
[0099] 13) The polished magnesium alloy AZ31 was immersed in the above-mentioned degreasing and deoiling aqueous solution, kept in a water bath at 50°C for 60 seconds, then alkaline washed with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polished with 400g / L nitric acid (ρ=1.42g / ml) at room temperature 25°C for 2 minutes; then rinsed once with deionized water and blown dry with cold air.
[0100] 2) Micro-arc oxidation film (MAO film for short)
[0101] 21) Prepare a micro-arc oxidation growth solution containing 0.049 M trisodium phosphate dodecahydrate and 0.18 M sodium hydroxide using deionized water according to the molar concentration;
[0102] 22) First, the magnesium alloy sample after degreasing and deoiling in step 1) is fixed in a polymethyl methacrylate electrolytic cell equipped with a stainless steel plate by copper wire, and then the micro-arc oxidation growth solution in step 21) is poured; the anode is AZ31 magnesium alloy, and the cathode is a stainless steel plate; the temperature of the micro-arc oxidation growth solution is 8°C, the reaction voltage is 350V, and the reaction time is 5min, to obtain a magnesium alloy covered with a MAO film;
[0103] 3) In situ growth of Co-Ni LDHs film
[0104] 31) According to the molar concentration, sodium nitrate, cobalt nitrate and nickel nitrate are dissolved in deionized water and mixed evenly to obtain an in-situ growth solution; wherein the molar concentration of sodium nitrate is 0.1 M, the molar concentration of cobalt nitrate is 0.15 M, and the molar concentration of nickel nitrate is 0.05 M; and then the pH value thereof is adjusted to 9 using a 0.1 M NaOH aqueous solution;
[0105] 32) Putting the magnesium alloy coated with MAO film prepared in step 2) into a polytetrafluoroethylene liner sleeve, then pouring the in-situ growth solution prepared in step 31) into the liner and placing the liner into the reactor, tightening it, and finally placing it in a drying oven for in-situ growth, the reaction temperature is 135° C., the reaction time is 12 h, and then washing and drying to obtain a magnesium alloy coated with Co-Ni LDHs film;
[0106] The cleaning and drying is specifically to first use running deionized water to clean the magnesium alloy sample covered with the Co-Ni LDHs film layer after the reaction in step 3) to remove the in-situ growth liquid attached to the surface, then put it into an ultrasonic cleaning machine in anhydrous ethanol for ultrasonic cleaning for 3 minutes, then clean it with deionized water, and dry it to obtain the Co-Ni LDHs film layer on the surface of the magnesium alloy micro-arc oxidation film;
[0107] 4) Coordination complex growth of ZIF-67 membrane
[0108] 41) Prepare two aqueous solutions containing 0.02 M cobalt nitrate and 1.4 M dimethylimidazole respectively;
[0109] 42) The magnesium alloy coated with the Co-Ni LDHs film layer prepared in step 3) is immersed in a mixed solution of the above two aqueous solutions, maintained at room temperature 25°C for 25 hours for coordination and complexation, and then washed and dried to obtain a magnesium alloy coated with a Co-Ni LDHs@ZIF-67 composite film layer; washed with deionized water and dried to obtain a Co-Ni LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film.
[0110] The present application tests the morphology, structure and performance of the Co-Ni LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film prepared in this embodiment, specifically:
[0111] 1) Appearance
[0112] The present application conducted an appearance morphology test on the Co-Ni LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film in Example 3, and the electron microscope scanning image thereof is shown in FIG. Figure 7 As shown in the figure, it can be seen that the Co-Ni LDHs nanosheets grown on the surface of the magnesium alloy MAO film are connected into sheets, and there are large pores between the sheets; after the growth of the Co-Ni LDHs@ZIF-67 composite film layer, the gaps between the LDHs nanosheets are obviously filled, and the LDHs become parallel to the direction of the substrate. The ZIF-67 grains on the surface are of different sizes, but the density of the composite film layer is significantly improved.
[0113] 2) Structural analysis
[0114] The present application tests the crystallinity of the Co-Ni LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film in Example 3, and its XRD spectrum is as follows: Figure 8 As shown in the figure, (003) and (006) crystal planes are characteristic crystal planes of LDHs. It can be seen from the figure that the Co-Ni LDHs coating has been successfully prepared. The diffraction peaks of the Co-Ni LDHs@ZIF-67 composite coating at 7.31°, 10.36°, 12.72°, 14.40°, 16.45° and 18.04° correspond to the (011), (002), (112), (013), (022) and (222) crystal planes of ZIF-67, respectively, indicating that it has good crystallinity.
[0115] 3) Electrochemical performance
[0116] The present application tests the electrochemical properties of the magnesium alloy surface film layer in Example 3 by using an electrochemical workstation, specifically:
[0117] The Tafel polarization curves of magnesium alloy AZ31, magnesium alloy coated with MAO film (curve MAO) and magnesium alloy coated with Co-Ni LDHs@ZIF-67 composite film (curve Co-Ni LDHs@ZIF-67) at the same coordinates measured by electrochemical workstation are as follows: Fig. 9 As shown, specifically:
[0118] The corrosion resistance test of the magnesium alloy protective film is represented by the electrochemical polarization curve (equipment model is Princeton4000A), in which the corrosion voltage of AZ31 magnesium alloy is -1.37V, the corrosion voltage of AZ31 magnesium alloy coated with MAO film after treatment under the conditions of Example 3 is -1.55V, and the corrosion voltage of AZ31 magnesium alloy coated with Co-Ni LDHs@ZIF-67 composite film is -0.69V, which is significantly improved compared with the corrosion voltage of magnesium alloy substrate, and the corrosion tendency is reduced. The corrosion rate and corrosion resistance are directly related to the corrosion current density. The corrosion current density of pure AZ31 magnesium alloy is 1.02×10 -5 Acm -2 The corrosion current density of the magnesium alloy covered with MAO film is 3.86×10 -6 A cm -2 However, the corrosion current density of the sample coated with Co-NiLDHs@ZIF-67 composite film after treatment under the conditions of Example 3 is 3.17×10 -9 A cm -2 The corrosion current density of the treated samples was reduced by 3 orders of magnitude compared with the magnesium alloy coated with MAO film; and by 4 orders of magnitude compared with the sample of AZ31 magnesium alloy. The above results fully demonstrate that the Co-Ni LDHs@ZIF-67 composite film has an effective corrosion inhibition effect on AZ31 magnesium alloy, and the Co-Ni LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film of the present invention has excellent corrosion resistance and can effectively protect the magnesium substrate.
[0119] Comparative Example 1
[0120] The method for preparing the LDHs film on the surface of the magnesium alloy provided in this comparative example comprises the following steps:
[0121] 1) Preprocessing
[0122] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0123] 12) Pretreatment of magnesium alloy: using 150#, 600#, 800#, 1200#, and 2000# sandpaper to grind the magnesium alloy, and using alcohol to ultrasonically clean it for five minutes and then dry it for use;
[0124] 13) The polished magnesium alloy AZ31 was immersed in the above-mentioned degreasing and deoiling aqueous solution, kept in a water bath at 50°C for 60 seconds, then alkaline washed with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polished with 400g / L nitric acid (ρ=1.42g / ml) at room temperature 25°C for 2 minutes; then rinsed once with deionized water and blown dry with cold air.
[0125] 2) In situ growth of Co-Fe LDHs film
[0126] 21) According to the molar concentration, sodium nitrate, cobalt nitrate and ferric nitrate are dissolved in deionized water and mixed evenly to obtain an in-situ growth solution; wherein the molar concentration of sodium nitrate is 0.1 M, the molar concentration of cobalt nitrate is 0.15 M, and the molar concentration of ferric nitrate is 0.05 M; and then the pH value thereof is adjusted to 9 using a 0.1 M NaOH aqueous solution;
[0127] 22) The degreased and deoiled magnesium alloy prepared in step 1) is placed in a polytetrafluoroethylene liner sleeve, and then the in-situ growth liquid prepared in step 21) is poured in and the liner is placed in a reactor, tightened, and finally placed in a drying oven for in-situ growth, the reaction temperature is 135° C., the reaction time is 12 h, and then washed and dried to obtain a magnesium alloy covered with a Co-Fe LDHs film;
[0128] The cleaning and drying is specifically to first use running deionized water to clean the magnesium alloy sample covered with the Co-Fe LDHs film layer after the reaction in step 2) to remove the in-situ growth liquid attached to the surface, then put it into an ultrasonic cleaning machine in anhydrous ethanol for ultrasonic cleaning for 3 minutes, then clean it with deionized water, and dry it to obtain the Co-Fe LDHs film layer on the surface of the magnesium alloy;
[0129] Comparative Example 2
[0130] The preparation method of ZIF-67 on the surface of magnesium alloy provided in this comparative example comprises the following steps:
[0131] 1) Preprocessing
[0132] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0133] 12) Pretreatment of magnesium alloy: using 150#, 600#, 800#, 1200#, and 2000# sandpaper to grind the magnesium alloy, and using alcohol to ultrasonically clean it for five minutes and then dry it for use;
[0134] 13) The polished magnesium alloy AZ31 was immersed in the above-mentioned degreasing and deoiling aqueous solution, kept in a water bath at 50°C for 60 seconds, then alkaline washed with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polished with 400g / L nitric acid (ρ=1.42g / ml) at room temperature 25°C for 2 minutes; then rinsed once with deionized water and blown dry with cold air.
[0135] 2) Coordination complex growth of ZIF-67
[0136] 21) Prepare two aqueous solutions containing 0.02 M cobalt nitrate and 1.4 M dimethylimidazole respectively;
[0137] 22) The degreased and deoiled magnesium alloy prepared in step 1) is immersed in a mixed solution of the above two aqueous solutions, maintained at room temperature 25°C for 25 hours for coordination and complexation, washed and dried to obtain a magnesium alloy coated with ZIF-67; washed with deionized water and dried to obtain a ZIF-67 sample on the surface of the magnesium alloy.
[0138] Comparative Example 3
[0139] The preparation method of the ZIF-67@Co-M LDHs composite film layer on the surface of the magnesium alloy micro-arc oxidation film provided in this comparative example is basically the same as that of Examples 1-3, except that the film preparation sequence on the surface of the MAO film is changed, and the ZIF-67 film is prepared first, and then the Co-M LDHs is prepared, specifically:
[0140] 1) Preprocessing
[0141] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0142] 12) Pretreatment of magnesium alloy: using 150#, 600#, 800#, 1200#, and 2000# sandpaper to grind the magnesium alloy, and using alcohol to ultrasonically clean it for five minutes and then dry it for use;
[0143] 13) The polished magnesium alloy AZ31 was immersed in the above-mentioned degreasing and deoiling aqueous solution, kept in a water bath at 50°C for 60 seconds, then alkaline washed with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polished with 400g / L nitric acid (ρ=1.42g / ml) at room temperature 25°C for 2 minutes; then rinsed once with deionized water and blown dry with cold air.
[0144] 2) Micro-arc oxidation film (MAO film for short)
[0145] 21) Prepare a micro-arc oxidation growth solution containing 0.049 M trisodium phosphate dodecahydrate and 0.18 M sodium hydroxide using deionized water according to the molar concentration;
[0146] 22) First, the magnesium alloy sample after degreasing and deoiling in step 1) is fixed in a polymethyl methacrylate electrolytic cell equipped with a stainless steel plate by copper wire, and then the micro-arc oxidation growth solution in step 21) is poured; the anode is AZ31 magnesium alloy, and the cathode is a stainless steel plate; the temperature of the micro-arc oxidation growth solution is 8°C, the reaction voltage is 350V, and the reaction time is 5min, to obtain a magnesium alloy covered with a MAO film;
[0147] 3) Coordination complex growth of ZIF-67 membrane
[0148] 31) Prepare two aqueous solutions containing 0.02 M cobalt nitrate and 1.4 M dimethylimidazole respectively;
[0149] 32) Soaking the magnesium alloy coated with the MAO film prepared in step 2) in a mixed solution of the above two aqueous solutions, maintaining it at room temperature of 25° C. for 25 hours for coordination and complexation, washing and drying to obtain a magnesium alloy coated with a ZIF-67 film; washing it with deionized water, and drying it to obtain a ZIF-67 film on the surface of the magnesium alloy micro-arc oxidation film;
[0150] 4) In situ growth of ZIF-67@Co-M LDHs membrane
[0151] 41) According to the molar concentration, sodium nitrate, cobalt nitrate, and iron nitrate or aluminum nitrate or nickel nitrate are dissolved in deionized water and mixed evenly to obtain an in-situ growth solution; wherein the molar concentration of sodium nitrate is 0.1 M, the molar concentration of cobalt nitrate is 0.15 M, and the molar concentration of iron nitrate / aluminum nitrate / nickel nitrate is 0.05 M; and then the pH values thereof are adjusted to 12, 8, and 9 respectively using a 0.1 M NaOH aqueous solution;
[0152] 42) placing the magnesium alloy coated with the ZIF-67 film prepared in step 3) into a polytetrafluoroethylene liner sleeve, then pouring the in-situ growth solution prepared in step 41) into the liner and placing the liner into the reactor, tightening it, and finally placing it in a drying oven for in-situ growth at a reaction temperature of 125° C. for a reaction time of 12 h, washing and drying to obtain magnesium alloys coated with ZIF-67@Co-Fe LDHs, ZIF-67@Co-Al LDHs, and ZIF-67@Co-Ni LDHs films;
[0153] The cleaning and drying are as follows: the magnesium alloy sample covered with the ZIF-67@Co-M LDHs film layer after the reaction in step 4) is first cleaned with flowing deionized water to remove the in-situ growth liquid attached to the surface, and then ultrasonically cleaned in anhydrous ethanol for 3 minutes using an ultrasonic cleaning machine, and then cleaned with deionized water and dried to obtain a ZIF-67@Co-M LDHs composite film layer on the surface of the magnesium alloy micro-arc oxidation film;
[0154] The present application conducted an XRD test on the ZIF-67@Co-M LDHs composite film layer on the surface of the magnesium alloy micro-arc oxidation film prepared in Comparative Example 3. The results are as follows: Fig.12 As shown in the figure, it can be seen that, except for the ZIF-67@Co-Fe composite film layer, the characteristic diffraction peaks of ZIF-67 in the other two film layers have basically disappeared, that is to say, the ZIF-67 structure in the composite film layer has been destroyed. Therefore, the method of first preparing ZIF-67 and then preparing LDHs on the surface of the magnesium alloy MAO film cannot make the two structures of ZIF-67 and LDHs coexist, so it is not universal.
[0155] In addition, the present application also observed the cross-sectional thickness and surface element distribution of the Mg-MLDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared in Examples 1, 2 and 3 by SEM and EDS. The results are as follows: Fig.10 As shown in the figure, it can be seen that when a single MAO layer is formed on the surface of the magnesium alloy, its thickness is 3.18±0.28μm; the thickness of the Mg-Al LDHs@ZIF-67 composite film layer on the surface of the micro-arc oxidation film of the magnesium alloy in Example 1 is 5.88±0.28μm; the thickness of the Mg-Fe LDHs@ZIF-67 composite film layer on the surface of the micro-arc oxidation film of the magnesium alloy in Example 2 is 7.70±0.19μm; the thickness of the Mg-Co LDHs@ZIF-67 composite film layer on the surface of the micro-arc oxidation film of the magnesium alloy in Example 3 is 5.97±0.15μm; Therefore, the Mg-M LDHs@ZIF-67 composite film layer on the surface of the MAO film of the magnesium alloy obtained by the preparation method of the present application, that is, the Mg-M LDHs@ZIF-67 composite film layer on the surface of the micro-arc oxidation film of the magnesium alloy prepared by the preparation method of the present application The thickness of the LDHs@ZIF-67 composite film layer is relatively thin. On the basis of the original MAO film layer, without significantly increasing the total thickness of the composite film, the composite film layer is prepared by combining MAO, LDHs and MOFs, which synergistically improves the corrosion resistance of the magnesium alloy.
[0156] Furthermore, the present application also tests the durability of the Co-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared in Examples 1, 2 and 3 by an electrochemical workstation. The specific test method is to immerse the composite film layer in a 3.5wt% NaCl solution for 14 days and then detect its Tafel polarization curve by an electrochemical workstation; the test results are as follows: Fig.11As shown, the corrosion voltage of the AZ31 magnesium alloy coated with the MAO film after immersion for 14 days is -1.46V, the corrosion voltage of the AZ31 magnesium alloy coated with the Co-Fe LDHs@ZIF-67 composite film after immersion for 14 days after treatment under the conditions of Example 1 is -1.48V, the corrosion voltage of the AZ31 magnesium alloy coated with the Co-Al LDHs@ZIF-67 composite film after immersion for 14 days after treatment under the conditions of Example 2 is -1.45V, and the corrosion voltage of the AZ31 magnesium alloy coated with the Co-Ni LDHs@ZIF-67 composite film after immersion for 14 days after treatment under the conditions of Example 3 is -1.44V. The corrosion rate and corrosion resistance are directly related to the corrosion current density. The corrosion current density of the magnesium alloy coated with the MAO film after immersion for 14 days is 4.76×10 -5 A cm -2 The corrosion current density of the magnesium alloy coated with the Co-Fe LDHs@ZIF-67 composite film after immersion for 14 days was 3.79×10 -7 Acm -2 The corrosion current density of the magnesium alloy coated with the Co-Al LDHs@ZIF-67 composite film after immersion for 14 days was 1.75×10 -7 A cm -2 The corrosion current density of the magnesium alloy coated with the Co-Ni LDHs@ZIF-67 composite film after immersion for 14 days was 2.32×10 -7 A cm -2 Compared with the magnesium alloy coated with MAO film after immersion for 14 days, the corrosion current density is reduced by 2 orders of magnitude. The above results can fully demonstrate that the Co-M LDHs@ZIF-67 composite film has excellent durability and long-term effective corrosion inhibition on AZ31 magnesium alloy. It has better corrosion resistance than single MAO, LDHs and ZIF-67 films, and can effectively protect the magnesium matrix.
[0157] In summary, the preparation method of the Co-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc film provided by the present invention is based on the magnesium alloy MAO film, a layer of Co-M LDHs film layer is in situ grown by a hydrothermal method, and then a Co-M LDHs@ZIF-67 composite film layer is obtained by a coordination reaction. The Co-M LDHs nanosheets are used to fill the micropores of MAO, making full use of the Co in the LDHs film layer. 2+The nucleation and growth of ZIF-67 nanoparticles are achieved, and ZIF-67 nanoparticles can also fill the interlamellar gaps of LDHs, making the composite film more compact and more corrosion-resistant. In addition, due to in-situ growth, the Co-M LDHs@ZIF-67 composite film is directly formed on the surface of the magnesium alloy MAO film, which improves the bonding strength and film-forming performance between the film and the substrate, and improves the feasibility of application in the industrial field. The Co-M LDHs@ZIF-67 composite film not only closes the pores of the MAO film, but also has the characteristics of corrosion resistance. Its performance is far better than that of the untreated magnesium alloy AZ31, and better than any single magnesium alloy surface corrosion protection film. After a large number of experiments, the inventors found that by using a traditional mature reactor on the MAO membrane layer, the purpose can be achieved through hydrothermal reaction and room-temperature complexation reaction, thereby generating a Co-MLDHs@ZIF-67 composite membrane layer with good bonding strength and good corrosion resistance; the operation steps of the present invention are simple, the raw materials are environmentally friendly and non-toxic, and the time consumption is short. Only a trace amount of external elements is required to obtain a Co-M LDHs@ZIF-67 composite membrane layer with better effect, and the energy consumption is lower.
[0158] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a Co-M LDHs@ZIF-67 composite film on the surface of a magnesium alloy micro-arc oxidation film, characterized in that: The steps include: 1) immersing the magnesium alloy in a micro-arc oxidation growth solution for micro-arc oxidation treatment to obtain a magnesium alloy covered with a MAO layer; 2) immersing the magnesium alloy coated with the MAO layer into an in-situ growth solution for in-situ hydrothermal reaction, washing and drying, and obtaining a magnesium alloy coated with a Co-M LDHs film layer; 3) The magnesium alloy coated with the Co-M LDHs film layer is immersed in a ZIF-67 growth solution for coordination complex reaction, and then washed and dried to obtain a magnesium alloy coated with a Co-M LDHs@ZIF-67 composite film layer, i.e., a Co-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film.
2. The method for preparing the Co-M LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film according to claim 1, characterized in that: In terms of substance concentration, the micro-arc oxidation growth solution includes an aqueous solution of 0.03-0.06 M trisodium phosphate dodecahydrate and 0.1-0.3 M sodium hydroxide.
3. The method for preparing the Co-M LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film according to claim 2, characterized in that: The process parameters of the micro-arc oxidation treatment are: the temperature of the micro-arc oxidation growth liquid is 5-10° C., the voltage of the micro-arc oxidation treatment is 300-400 V, and the time is 2-8 min.
4. The method for preparing the Co-M LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film according to claim 1, characterized in that: In terms of molar concentration, the in-situ growth solution includes 0.1-0.2M cobalt nitrate, 0.05-0.1M sodium nitrate, and a mixed aqueous solution of any one of 0.03-0.08M iron nitrate, 0.03-0.08M aluminum nitrate, or 0.03-0.08M nickel nitrate.
5. The method for preparing the Co-M LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film according to claim 4, characterized in that: The process parameters of the in-situ hydrothermal reaction are: reaction temperature of 125-145° C., and reaction time of 8-16 h.
6. The method for preparing the Co-M LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film according to claim 1, characterized in that: In terms of molar concentration, the ZIF-67 growth solution includes a mixed aqueous solution of 0.01-0.04 M cobalt nitrate and 1.0-1.5 M dimethylimidazole.
7. The method for preparing the Co-M LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film according to claim 6, characterized in that: The process parameters of the coordination complex reaction are: reaction temperature is room temperature of 20-30° C., and reaction time is 16-32 hours.
8. The method for preparing the Co-M LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film according to claim 1, characterized in that: The method also includes pre-treatment of the magnesium alloy before micro-arc oxidation treatment, specifically: grinding the magnesium alloy substrate with 150, 600, 800, 1200, and 2000# sandpaper respectively, ultrasonically cleaning with alcohol and then drying; and then degreasing and deoiling the ground magnesium alloy substrate.
9. The method for preparing the Co-M LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film according to claim 8, characterized in that: Measured in terms of mass concentration, the degreasing and deoiling solution used in the degreasing and deoiling process is an aqueous solution comprising 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate, measured in terms of mass volume concentration.
10. Application of the Co-MLDHs@ZIF-67 composite film layer on the surface of a magnesium alloy MAO film prepared by the preparation method according to any one of claims 1 to 9 in the fields of aerospace, automobile, medical equipment and 3C digital.
Citation Information
Patent Citations
Preparation method of micro-arc oxidation film-ZIF-8-GO / LDHs film on magnesium alloy surface
CN113355717A
Micro-arc oxidation magnesium alloy surface one-step in-situ generated Zn-MOF coating and preparation method thereof
CN113668035A
Photo-thermal antibacterial corrosion-resistant medical magnesium alloy composite coating and preparation method thereof
CN116970951A
